2016
DOI: 10.1158/1940-6207.capr-16-0026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walnut Consumption on Colon Carcinogenesis and Microbial Community Structure

Abstract: Walnuts are composed of a complex array of biologically active constituents with individual cancer-protective properties. Here, we assessed the potential benefit of whole walnut consumption in a mouse tumor bioassay using azoxymethane. In study 1, a modest reduction (1.3-fold) in tumor numbers was observed in mice fed a standard diet (AIN-76A) containing 9.4% walnuts (15% of total fat). In study 2, the effects of walnut supplementation was tested in the Total Western Diet (TWD). There was a significant reducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 61 publications
10
50
1
Order By: Relevance
“…Overall, our results suggest that standardized basal diets, such as the AIN93G, may underestimate or fail to demonstrate the efficacy of bioactives such as GTE because mice fed these diets may have an increased resilience to CRC. Rosenberg et al also had a similar finding in a study comparing the AIN-76A diet to our TWD, where supplementation with 7% (w/w) walnut suppressed tumor development in mice fed TWD, but not AIN-76A [50]. Importantly, in the present study, if the AIN93G diet had been used as the only basal diet to investigate the effects of GTE on CRC, we would have reported that GTE had no effect.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, our results suggest that standardized basal diets, such as the AIN93G, may underestimate or fail to demonstrate the efficacy of bioactives such as GTE because mice fed these diets may have an increased resilience to CRC. Rosenberg et al also had a similar finding in a study comparing the AIN-76A diet to our TWD, where supplementation with 7% (w/w) walnut suppressed tumor development in mice fed TWD, but not AIN-76A [50]. Importantly, in the present study, if the AIN93G diet had been used as the only basal diet to investigate the effects of GTE on CRC, we would have reported that GTE had no effect.…”
Section: Discussionsupporting
confidence: 87%
“…Rosenberg et al. also had a similar finding in a study comparing the AIN‐76A diet to our TWD, where supplementation with 7% (w/w) walnut suppressed tumor development in mice fed TWD, but not AIN‐76A . Importantly, in the present study, if the AIN93G diet had been used as the only basal diet to investigate the effects of GTE on CRC, we would have reported that GTE had no effect.…”
Section: Discussionsupporting
confidence: 87%
“…Recent evidence from our lab and others suggest that the phenolic compound (+)-catechin, and its dimeric form procyanidin B2 can alter the biophysical properties of cell plasma membranes[82,83] (Figure 2), similar to what has been observed with other MTDB’s such as n-3 PUFA and curcumin[8,8486]. Interestingly, walnuts have been shown to inhibit the growth of human cancer cell lines[87,88], and colon cancer in mouse models[8991], similar to what has been demonstrated with other MTDB’s such as n-3 PUFA[8,23,69,9295]. In addition, a meta-analysis concluded that nut consumption is associated with decreased risk of cancer mortality, further supporting the inclusion of nut consumption for cancer prevention[96].…”
Section: Introductionmentioning
confidence: 62%
“…1. The separation of fatty acids using gas-chromatography 1 Average data for oils from 5 different varieties of Juglans regia L. grown in Greece; 2 Average data for oils from 8 different v arieties of Juglans regia L. grown in Argentina; 3 Average data for oils from 6 different varieties of Juglans regia L. grown in Portugal; 4 Average data for oils from 11 different varieties of Juglans regia L. grown in Hungary Table 1 FATTY ACIDS PROFILE FOR WALNUTS OILS COMPARED WITH THE LITERATURE DATA Table 2 THE SUM OF DIFFERENT FATTY ACIDS CLASSES AS FOLLOWING: SATURATED, MONOSATURATED AND POLYSATURATED antioxidants reactions, the blue colour of the DPPH solution may reach a yellow colour, in accordance with the hydrogen donating ability of the antioxidants. The DPPH• free radical scavenging activities of (i) walnut oil, (ii) lipophilic fraction (insoluble in methanol), and (iii) hydrophilic fraction (soluble in methanol) were evaluated.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Walnuts oil is dietary sources of essential fatty acids which could not be synthesized in the body and must be supplied by food [1]. Recently, has been demonstrated that walnut consumption could protect against colon cancer by changes of the gut microbiome [2]. As well, cold press oil obtained from walnuts could decrease the sugar concentrations in patients with diabetes mellitus type 2 [3].…”
mentioning
confidence: 99%